2020
DOI: 10.4103/jispcd.jispcd_444_19
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the suture-less anterior releasing incision in a triangular flap design on postoperative healing following surgical removal of impacted mandibular third molars

Abstract: A BSTRACT Objectives: The objective of this study was to determine the effect of suture-less anterior releasing incisions on postoperative wound healing following surgical removal of impacted mandibular third molars. Materials and Methods: A total of 112 patients were included in the study. Group 1 had 56 patients in which the anterior releasing incision was not sutured postoperatively, and group 2 had 56 patients, in whom the anterior releasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…As in earlier studies, Nayak et al . used a suture-less anterior releasing incision ( 30 ), the results showed that the suture-less incision decreased postoperative swelling and edema; however, the periodontal healing was poor when compared to the sutured cases. Moreover, the lower the third molar are impact, the larger bone defect will be.…”
Section: Discussionmentioning
confidence: 99%
“…As in earlier studies, Nayak et al . used a suture-less anterior releasing incision ( 30 ), the results showed that the suture-less incision decreased postoperative swelling and edema; however, the periodontal healing was poor when compared to the sutured cases. Moreover, the lower the third molar are impact, the larger bone defect will be.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of sutures have been used in dental extractions: silk has been the most common suture material in M3M surgery, and the main criticism it has received is regarding the bacterial biofilm formation over it [ 4 ]. With regards to suture technique in M3M surgery, international literature provides sutureless techniques, single suture techniques, different knotless suture techniques and the use of sutureless release incision techniques: each of these reported small advantages in terms of postoperative symptoms, time spent for suture and time saved after surgery [ 5 , 6 , 7 , 8 , 9 ]. Drainage inside the wound after M3M extraction and its retention until suture removal may have a role to reduce postoperative complications, too [ 10 ].…”
Section: Introductionmentioning
confidence: 99%